Careers in biomedical engineering - Levin-Epstein, Michael D. (Academic Press, 2019)
Careers in Biomedical Engineering offers readers a comprehensive overview of new career opportunities in the field of biomedical engineering. The book begins with a discussion of the extensive changes which the biomedical engineering profession has undergone in the last 10 years. Subsequent sections explore educational, training and certification options for a range of subspecialty areas and diverse workplace settings. As research organizations are looking to biomedical engineers to provide project-based assistance on new medical devices and/or help on how to comply with FDA guidelines and best practices, this book will be useful for undergraduate and graduate biomedical students, practitioners, academic institutions, and placement services.